2009
DOI: 10.1245/s10434-008-0190-x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Chemotherapy Does Not Increase Morbidity or Mortality of Hepatic Resection for Colorectal Cancer Metastases

Abstract: Hepatic metastasis from colorectal cancer (mCRC) is best treated with a multidisciplinary approach. Conflicting data exist regarding the impact of preoperative chemotherapy on morbidity and mortality after hepatectomy. We hypothesized that preoperative chemotherapy does not adversely impact complications or mortality associated with hepatectomy. A retrospective analysis was performed and included patients with mCRC who underwent hepatectomy from 1996 to 2006. Patients were separated into two groups: those who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
49
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 30 publications
3
49
3
Order By: Relevance
“…In this sample of patients, estimated 5-year overall survival was 64.9%, a higher result than that found in other principal studies so far (4,11,12,21) . This can be explained by the relatively short median follow-up time (29 months) and the extremely rigorous selection of patients submitted to surgical resection, especially in the 1st years of the study.…”
Section: Discussioncontrasting
confidence: 65%
“…In this sample of patients, estimated 5-year overall survival was 64.9%, a higher result than that found in other principal studies so far (4,11,12,21) . This can be explained by the relatively short median follow-up time (29 months) and the extremely rigorous selection of patients submitted to surgical resection, especially in the 1st years of the study.…”
Section: Discussioncontrasting
confidence: 65%
“…In particular, no patient developed hepatic failure. In the literature, several studies reported no increase of morbidity and mortality after preoperative chemotherapy (24)(25)(26). In the series of Aloia et al (5), patients who had received more than 12 cycles of preoperative chemotherapy had higher risk of reoperation and a longer hospital stay.…”
mentioning
confidence: 99%
“…The multidisciplinary team must determine whether a margin-negative resection is achievable and that an adequate amount of liver with intact vascular inflow and outflow and biliary drainage will remain post-resection in order to prevent post-operative hepatic failure. The volume of liver parenchyma that will remain after resection, i.e., the future liver remnant (FLR), is of paramount importance in hepatic resections [11][12][13]. Conventionally 20 % of the total liver volume has been regarded as the minimum safe FLR in a patient with normal hepatic function [7]; however, an FLR of 30-40 % is necessary if the patient has received cytotoxic chemotherapy, since chemotherapeutic agents used to treat CRC cause hepatic injury, such as steatosis and sinusoidal obstruction with oxaliplatin and steatohepatitis with irinotecan [12,14].…”
Section: Decision Making: Patient Evaluation and Selection For Resectionmentioning
confidence: 99%